PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI 31 PEKANBARU - Martina Wati Sitorus; Jesi Alexander Alim; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACT : The proplem in this research is the low math learning outcomes fifth grade students of SD Negeri 31 Pekanbaru is the average of 64.5 with the KKM 73 . This is caused by the lack of students’ participation in performing tasks. Beside it, the lack of students’ enthusiasm in learning also had an impact on this problem, where the teachers were still using lecture method. In addition, the teachers did not provide appreciation to the students as a motivation.The purpose of this research is to improve the results of learning mathematics by applying cooperative learning model type Jigsaw. In Jigsaw cooperative learning model that engages students to work together and positive interdependence with his friend , the courage to train students in expressing their opinion and explain the matter experts grouped under their responsibility to their friends grouped origin. With the formulation of the problem " Is the application of the cooperative learning model types Jigsaw to improve learning outcomes math fifth grade students of SD Negeri 31 Pekanbaru ? " . The subject of this research is the fifth grade students of SD Negeri 31 Pekanbaru as many as 20 students with 9 males and 11 females. The average value of learning result of the students has increased from 64, 5 to UH I 75, 5. The increased amount of initial score to level UH I is 11 points. In the level UH II, the score has increased to 83, 9. The increased amount from UH I to UH II is 8.4 points. The total increase in overall is 19, 4 points. And in classical students have completed the percentage of 85 % . From the data, it can be concluded that the application of Cooperatif Learning types Jigsaw to improve learning outcomes fifth grade students of SD Negeri 31 Pekanbaru.Key words: Cooperative Learning types Jigsaw, the result of learning Mathematics